2019
DOI: 10.17219/dmp/104602
|View full text |Cite
|
Sign up to set email alerts
|

Porcelain sectional veneers, an ultra-conservative technique for diastema closure (three-dimensional finite element stress analysis)

Abstract: Background. Diastema can be closed using conservative and non-conservative techniques. Composite resin wings and ceramic veneers are the most common treatment options if there is no indication for orthodontic treatment. A novel ultra-conservative technique has been introduced to the practice, i.e., porcelain sectional veneers can be fabricated with no or minimum preparation. However, porcelain is known for its poor mechanical properties and the long-term survival of such restorations is questionable. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Higher stress concentrations in the ceramic were observed for thicker resin cement layers, which increased the risk of failure when the ceramic was subjected to higher temperatures [28]. A similar finite element analysis by the same authors [29] showed an increased stress concentration when forces were applied directly to the ceramic, particularly at higher inclination angles (137°)…”
Section: Finite Element Stress Analysismentioning
confidence: 75%
“…Higher stress concentrations in the ceramic were observed for thicker resin cement layers, which increased the risk of failure when the ceramic was subjected to higher temperatures [28]. A similar finite element analysis by the same authors [29] showed an increased stress concentration when forces were applied directly to the ceramic, particularly at higher inclination angles (137°)…”
Section: Finite Element Stress Analysismentioning
confidence: 75%
“…Finally, occlusion must also be carefully considered, since high stress could be distributed at direct oclusal and inclined forces (15) , thus, direct contact to the interface must be avoided to ensure the integrity of the restoration…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, ceramic veneers show excellent clinical performance [51][52][53] and, in a recent systematic review and meta-analysis, the estimated overall cumulative survival rate of glass-ceramic and feldspathic porcelain veneers was 89% in a median follow-up period of 9 years [54]. However, at the moment, there is no clinical study reporting on the longevity of ceramic sectional veneers and it is possible that their survival rate would not be as good as conventional ceramic veneers because laboratory studies show high stress concentrations at the bonding interface of ceramic sectional veneers [55]. In a three-dimensional finite element analysis, ceramic sectional veneer diastema restoration shows a significantly higher stress concentration than direct composite diastema restoration and the larger the size of the diastema, the higher the von Mises stress value.…”
Section: Discussionmentioning
confidence: 99%